Adaptable imaging package for remote vehicles. (October 2017) - Liardon, Jean-Luc; Barry, D.A.
Graphical abstract: Abstract: An easy-to-customize, low-cost solution for remote imagery is described. The system, denoted ImPROV (Imaging Package for Remote Vehicles), supports multiple cameras, live streaming, long-range encrypted communication using mobile networks, positioning and time-stamped imagery, etc. The adaptability of the system is demonstrated by its deployment on different remotely operated or autonomous vehicles, which include model aircraft, drones, balloon, kite and a submarine.